2012
DOI: 10.1021/cs200530e
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Hydrodesulfurization Catalyst Obtained by Mo(CO)6 Grafting on the Metal–Organic Framework Ni2(2,5-dihydroxoterephthalate)

Abstract: The Metal−Organic Framework, [Ni 2 (dhtp)] (H 4 dhtp = 2,5-dihydroxyterephthalic acid) was modified by gas-phase grafting of Mo(CO) 6 at the gram-scale via a post-synthesis modification approach. A highly dispersed well-defined bimetallic material containing the [Ni 2 (dhtp)Mo(CO) 3 ] fragment either in the staggered or in the eclipsed conformation was obtained, with a maximum coverage of 50% mol , as shown by multitechnique characterization: IR (diagnostic ν(CO) = 1996, 1972, 1926, 1885, and 1797 cm −1 ), N 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…It is known that the properties of supported oxide precursors influence the features of supported sulfide catalysts even though sulfidation of oxides is not a topotactic transition . For unsupported catalysts, these relations have been recently discussed . In this work, the LCF of the XANES at the Ni K‐edge during sulfidation (Figure ) indicate that the sulfidation of Ni is relatively difficult if the precursor is crystalline as in the bimetallic NiW Ox and NiMo Ox precursors.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is known that the properties of supported oxide precursors influence the features of supported sulfide catalysts even though sulfidation of oxides is not a topotactic transition . For unsupported catalysts, these relations have been recently discussed . In this work, the LCF of the XANES at the Ni K‐edge during sulfidation (Figure ) indicate that the sulfidation of Ni is relatively difficult if the precursor is crystalline as in the bimetallic NiW Ox and NiMo Ox precursors.…”
Section: Discussionmentioning
confidence: 63%
“…Such sulfides have been reported to have high activity and stability in most demanding hydrotreating conditions . Although several aspects of routes to prepare unsupported catalysts, such as impact of precursor materials, sulfidation procedures, and concentration of the promoters on the activity of working catalysts have been considered, the reasons for the high activity of such materials that could be related to catalyst preparation has not been deduced.…”
Section: Introductionmentioning
confidence: 99%
“…Highly selective solid catalysts were prepared by encapsulating catalyticallyactive sites within well-defined frameworks, which have specific pore dimensions and topologies [14][15][16][17]. For example, it was recently demonstrated that asymmetric hetero-Diels-Alder reactions can be activated by embedding catalytically active Ti(IV) ions within NbO-type chiral metal-organic frameworks [18].…”
Section: Introductionmentioning
confidence: 99%
“…23 Similarly, the MOF [Ni 2 (dhbd)] (dhbd = 2,5-dihydroxybenzene-1,4-dicarboxylate) can be metallated through chemical vapor deposition (CVD) with sublimation of Mo(CO) 6 into the MOF pores. 24 Again infrared spectroscopy supports the formation of (dhbd)Mo(CO) 3 species on the MOF framework, and microanalysis indicates that half of the dhbd 2− ligands are metallated. This material was degraded under an atmosphere of dihydrogen-hydrogen sulfide to give a heterogeneous catalyst for hydrodesulfurization reactions.…”
Section: Grafting Onto Arene Ringsmentioning
confidence: 79%